Quality Management in Building Quality School Branding - Balu, Hidayanti; Apriyanti, Meli; Arifin, Zainal (Studia Manageria, 2024)
This study aims to explore the quality management process at Madrasah Ibtidaiyah Fatimiyah Yogyakarta, which is dedicated to establishing a leading educational institution. The subjects of this research are the headmaster and teachers at Madrasah Ibtidaiyah Fatimiyah Yogyakarta. In this study, observation and interviews were used as data collection techniques. The data analysis techniques used in this study are data condensation, data presentation, and conclusion drawing. The results of the study show that in order to build the branding of a quality school at Madrasah Ibtidaiyah Fatimiyah Yogyakarta, the process of Islamic based quality management is realized through several stages namely planning, implementation, and evaluation. Quality management plays a very important role in building quality branding for a school, as has been proven at Madrasah Ibtidaiyah Fatimiyah Yogyakarta. The branding of Madrasah Ibtidaiyah Fatimiyah Yogyakarta as an outstanding school is that it is a madrasah integrated with a pesantren (Islamic boarding school) for the tahfizul Qur’an program. Madrasah Ibtidaiyah Fatimiyah Yogyakarta has successfully integrated the principles of quality management into various aspects of the madrasah’s activities, ranging from resource management, curriculum development, to the implementation of teaching and learning. By implementing quality management, the madrasah is able to provide educational services that not only meet but also exceed the expectations of the community. This has created a positive reputation in the community, which recognizes MI Fatimiyah Yogyakarta as a quality school, making it the primary choice for those seeking the best education. The implications of this study are that it provides valuable knowledge not only for Madrasah Ibtidaiyah Fatimiyah Yogyakarta but also for the advancement of educational in a broader context.